2022
DOI: 10.1111/ijlh.13788
|View full text |Cite
|
Sign up to set email alerts
|

Significance of WT1 and multiparameter flow cytometry assessment in patients with chronic myelomonocytic leukemia receiving allogeneic hematopoietic stem cell transplantation

Abstract: Introduction:The objective of this study was to investigate the clinical significance of minimal residual disease (MRD) monitoring through Wilms tumor 1 (WT1) gene expression and multicolor flow cytometry (FCM) in patients with chronic myelomonocytic leukemia (CMML) after allogeneic hematopoietic stem cell transplantation (allo-HSCT).Methods: For this purpose, WT1 gene expression and the CMML-related abnormal immunophenotype were examined using real-time quantitative polymerase chain reaction and FCM, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years 4,35,50 . We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan 16,22,27 and China, 6,43,49,56–63 ), and the results showed that the median age of CMML patients in Eastern countries was younger (38–70 years vs. 44–73 years), and the median age of CMML patients undergoing allo‐HSCT was similar in Eastern and Western countries (38–63 years vs. 44–64 years). However, the age of CMML patients undergoing allo‐HSCT was lower in both Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…According to CMML epidemiological statistics, almost 90% of cases occur in patients older than 60 years 4,35,50 . We reviewed the literatures on the age of CMML patients in Western (Germany, 29,30,51 France, 13,19,52 America, 8,11,12,15,17,20,25,26,28,40,53,54 Italy, 39,55 Greece, 14 and Denmark, 24 ) and Eastern countries (Japan 16,22,27 and China, 6,43,49,56–63 ), and the results showed that the median age of CMML patients in Eastern countries was younger (38–70 years vs. 44–73 years), and the median age of CMML patients undergoing allo‐HSCT was similar in Eastern and Western countries (38–63 years vs. 44–64 years). However, the age of CMML patients undergoing allo‐HSCT was lower in both Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found it to be predictable, whereas other did not (23,24,35,47). However, newer prognostic tools have been proposed, such as the CPSS-mol, the CPSS-P, and the CPSS transplantspecific, which have incorporated the prognostic importance of mutations that can predict outcome in transplanted patients, as this has been shown in several retrospective studies (23,50,74,91,93). Using these tools might help to better distinguish the transplantation risk group.…”
Section: Discussion-conclusion and Current Recommendationsmentioning
confidence: 99%
“…Both techniques demonstrated a high level of prognostic value and could predict posttransplant relapse. The significance of the presence of WT1 mutations was not investigated (91).…”
Section: Factors With Prognostic Importance For Allogeneic Stem Cell ...mentioning
confidence: 99%
“…Patients with a detectable mutation pre-and post-transplant had a higher incidence of relapse (50%) than those in which the mutation was only detected before the transplant but not after (15%) [153]. These molecular markers, the CSF3R T618I mutation, and the detection of MRD with PCR for WT1 or flow cytometry can be used as predictors of relapse post-transplant [154,155].…”
Section: Studies Of Acml Mds-mpn-nos and Mds/mpn Combinationsmentioning
confidence: 99%